En approximativ beräkningsmetod för beräkning av kostnaden per kilowattimme energi - Anpassad för dieselgeneratorer ombord på befintlig fartygsflotta - Johansson, Tomas; Thelin, Karl (My University, 2014)
Shipping is a competitive, global market. Because of this, shipping companies and their crews constantly need to make decisions that affect them economically. These decisions affect areas such as electrical power generation and consumption. More specifically these decisions can be about whether or not to use cold ironing. In order to make an informed decision, a correct estimation of the actual cost of power production is needed. This bachelor thesis, written in Swedish, makes an attempt to create an approximate method to calculate the cost per kWh of electrical power generated onboard with diesel generators. Aiming to give a result that reflects the condition the vessel is operating in. The ambition is that the calculation-method will function as an economical tool for shipping companies and crews, to help them conceptualize the effects of energy savings onboard. In order to create the calculation-method a series of questions are formulated and thereafter answered. The questions covers areas such as, what costs are included in the power production and how should data that are difficult to calculate be handled, etc. From these questions the theoretical base, which the work is built on, is gathered. This is not a paper that utilizes quantitative or qualitative studies. Instead a comprehensive literature review of books, scientific articles and product guides, spanning a multitude of areas, is used. The main focus is on areas that affect production cost of electricity. Some of the information needed is gathered through contact with employees’ of shipping companies and onboard ships. The collected information is compiled to a calculation-method comprised of seven different cost modules. The aim is that the usability of the calculation-method will be such that crews’ onboard ship will be able to use it. Therefore great emphasis is placed on the usability of the calculation-method. In an example, the calculation-method and its usability is tested with real data from a specific ship. A result of the cost per kWh electrical energy onboard that ship is attained, and present on page 30. The calculation method for the cost of producing electricity with diesel generators is meant to be used onboard the existing marine fleet. The calculation method is thus not suitable for use in shore based power plants.
Keywords: Energi; Transport; Annan teknik; Energy; Transport; Other Engineering and Technologies